Transnational migration, gender and rights - Leonard, Liam; Sollund, Ragnhild Aslaug, 1959- (Advances in ecopolitics ;, 2012)
The last decades have shown an increase in the migration from poor and conflict ridden states to the affluent peaceful north. Part of this migration is constituted by refugees and asylum seekers, while the other part, grossly put, is constituted by labour migrants who seek to improve their lives and future prospects through their work power. There are of course not only push factors causing migrants to leave, but also pull factors as when the middle classes enjoy an increase in their living standards which cause them to employ domestic help in their homes. Different regulations apply for migrants within different national contexts and also within the same nation and have different impact on the migrants manoeuvring possibilities and rights, and may leave them vulnerable to exploitation. As migration is gendered in that different motivations often exist for men and women, so are the possibilities that are offered, exemplified by the fact that very many women migrate as domestic workers, as nannies, or as au pairs, yet basically perform the same duties but are defined differently according to the rules that apply. As the work the female migrants perform is very often and traditionally regarded as womens work it does not qualify as real work and, consequently, it is not necessary to pay them a proper salary. This book examines the vulnerability caused by migration or rather the fact that the vulnerability of women may cause a forced migration and the ways in which this is dealt with by national authorities in affluent European states.